2018
DOI: 10.3233/jad-170988
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Protective Effects of Mitochondrial Division Inhibitor 1 and Mitochondria-Targeted Small Peptide SS31 in Alzheimer’s Disease

Abstract: The purpose our study was to determine the synergistic protective effects of mitochondria-targeted antioxidant SS31 and mitochondria division inhibitor 1 (Mdivi1) in Alzheimer’s disease (AD). Using biochemical methods, we assessed mitochondrial function by measuring the levels of hydrogen peroxide, lipid peroxidation, cytochrome c oxidase activity, mitochondrial ATP and GTPase Drp1 enzymatic activity in mutant AβPP cells. Using biochemical methods, we also measured cell survival and apoptotic cell death. Amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 57 publications
4
80
0
1
Order By: Relevance
“…This reduction is mainly because of reduced Drp1 levels and GTPase Drp1 enzymatic activity. Our observations are strongly supported by earlier cell culture studies in AD (28,40) and HD (31). Another supporting evidence based on transmission electron microscopy (1) in N2a cells treated with Mdivi-1, (2) Drp1 overexpressed plus Mdivi-1 and (3) Drp1 RNA silenced plus Mdivi-1-treated is that significantly increased length of mitochondria and reduced mitochondrial number are likely because of reduced GTPase Drp1 enzymatic activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This reduction is mainly because of reduced Drp1 levels and GTPase Drp1 enzymatic activity. Our observations are strongly supported by earlier cell culture studies in AD (28,40) and HD (31). Another supporting evidence based on transmission electron microscopy (1) in N2a cells treated with Mdivi-1, (2) Drp1 overexpressed plus Mdivi-1 and (3) Drp1 RNA silenced plus Mdivi-1-treated is that significantly increased length of mitochondria and reduced mitochondrial number are likely because of reduced GTPase Drp1 enzymatic activity.…”
Section: Discussionsupporting
confidence: 91%
“…It has been well established that increased Drp1 activity produces excessively fragmented mitochondria in AD neurons (18,23,38–40). Excessive mitochondrial fragmentation is a major feature in neurodegenerative diseases (16–18,20,23,40–44). Reduction in GTPase Drp1 activity is considered as a therapeutic strategy in diseases that involve increased mitochondrial fragmentation and mitochondrial dysfunction (18,20,31).…”
Section: Discussionmentioning
confidence: 99%
“…In one of AD murine models, the SS31 reduced Aβ peptide production, mitochondrial dysfunction, and enhanced mitochondrial biogenesis and synaptic activity (Calkins et al, 2011; Reddy et al, 2017). Recently, a combination of SS31 and the mitochondrial division inhibitor 1 (Mdivi1) was tested in cultured AD cells with positive effects, suggesting that a combined treatment of mitochondria-targeted antioxidants could have higher effectiveness (Reddy et al, 2018).…”
Section: Mitochondrial Therapies In Admentioning
confidence: 99%
“…In this review, we have illustrated the fundamental role of Mfn2 in mitochondrial function in health and disease, in particular in AD. Recently, different authors have indicated how perturbations in mitochondrial dynamics, particularly in fission and fusion proteins, Drp1, Fis1, OPA1, and Mfn2, can contribute to neuropathology [54][55][56].…”
Section: Mfn2 As a Potential Target In Alzheimer's Diseasementioning
confidence: 99%